2017
DOI: 10.3384/diss.diva-142870
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic modelling - a BOLD response to the fMRI information loss problem

Abstract: To everyone who let me take a look at their brain, particularly the pilots; the test participants get all the credit, even though you are the ones spending all that extra time in the scanner to sort out the messes we make.Without you, none of our experiments would be running at all.i Populärvetenskaplig sammanfattningNär vi studerar hur människans hjärna fungerarär det viktigt att använda en teknik somär säker för försökspersonerna och samtidigt ger relevant information om hjärnan. Funktionell Magnetresonansto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Nevertheless, once such an interconnected model is in place, it can be used to provide a new updated ability to use a model to infer CMRO 2 , compared to the highly simple model that is used presently (47). Fourth, such integrated analyses could also be useful in clinical contexts, since multiple variables analysed together would provide an integrated understanding of the brain, with the potential for new biomarkers and mechanistic insights regarding patient screening, stratification, and monitoring (48). Finally, a future metabolic-NVC model can also be used in multi-organ digital twin models, that also can be used for a variety of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, once such an interconnected model is in place, it can be used to provide a new updated ability to use a model to infer CMRO 2 , compared to the highly simple model that is used presently (47). Fourth, such integrated analyses could also be useful in clinical contexts, since multiple variables analysed together would provide an integrated understanding of the brain, with the potential for new biomarkers and mechanistic insights regarding patient screening, stratification, and monitoring (48). Finally, a future metabolic-NVC model can also be used in multi-organ digital twin models, that also can be used for a variety of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, once such an interconnected model is in place, it can be used to provide a new updated ability to use a model to infer CMRO 2 , compared to the highly simple model that is used presently [56]. Fourth, such integrated analyses could also be useful in clinical contexts, since multiple variables analysed together would provide an integrated understanding of the brain, with the potential for new biomarkers and mechanistic insights regarding patient screening, stratification, and monitoring [58]. Finally, a future metabolic-NVC model can also be used in multi-organ digital twin models, that also can be used for a variety of applications.…”
Section: Nvc Modelmentioning
confidence: 99%
“…It has been found that a signal recording scheme with a low temporal sampling rate (e.g., fMRI) can not directly reflect the underlying stimulustriggered neural activities [59]. Before being recorded by those low temporal resolution techniques, the shortterm neural activity variations need to accumulate until the variations are intense and robust enough [59], accompanied by significant loss in neural activity information [59][60][61][62]. A classical solution towards this limitation is to develop high temporal resolution recording techniques (e.g., multiphoton microscopy [63][64][65]).…”
Section: A Significance Of Our Workmentioning
confidence: 99%